A Comprehensive Review of Brucella canis: Zoonotic Risks and Preventive Strategies - Rasool, Akhter; Kannan, Porteen (The Indian Journal of Animal Reproduction, 2023)
Brucella canis, a zoonotic agent, primarily infects dogs and wild Canidae. Infection is notably suspected in dogs exhibiting epididymitis, infertility, or diskospondylitis. Recent reports indicate a growing incidence of Brucella canis infections in dogs, particularly among those imported into the UK from Eastern Europe. Although human infections by B. canis are relatively uncommon, clinical manifestations are typically mild, yet severe cases can potentially lead to septicemia. The disease in humans is incurable and spreads through contact with fluids from infected animals. Various diagnostic protocols, including Real-time PCR, Rapid slide agglutination test (RSAT), and Complement fixation test (CFT), are employed for the diagnosis of canine brucellosis. These serological tests play a crucial role in diagnosing canine brucellosis. Given the potential zoonotic risks, it is imperative to consistently include B. canis in diagnostic algorithms for canine diseases.
Keywords: Brucella canis; Diagnosis; Prevention; Zoonosis